Ultraviolet detector for improving performance of GaN-based Schottky structure and its making method - ZHAO DEGANG; YANG HUI; LI XIANGYANG; LIANG JUNWU; GONG HAIMEI (2008)
The invention is concerned with the the ultraviolet (UV) detector to improve the GaN group pin structure performance. It includes substrate, the nucleation layer, the high pH indicator module N ohmic contact layer, the source layer, the GaN contact electrode, the ohmic contact layer and the ohmic contact electrode. The components are overlapping one with another from the bottom to the top follows the statement orderly, expect the point or ring structure ohmic contact electrode that is on the both sides above the ohmic contact layer.